Sociopsychotechnological Predictors of Individual’s Social Loafing in Virtual Team - Juneman Abraham; Melina Trimutiasari (Institute of Advanced Engineering and Science, 2015)
The rapid development of technology and the demands of the workers to be productive have made efficiency and effectiveness of virtual team collaboration is becoming increasingly urgent lately. Therefore, it is important to identify the variables undermining the efficiency and effectiveness. This study aimed to investigate the role of perceived usefulness, perceived ease of use, and perceived playfulness of online collaboration tool (as elements of technology acceptance) and xenophobia in predicting social loafing (at the individual level)─a social psychological phenomenon that shows the declining performance of the individual when working in the group. The contribution of this research is its attempt to combine social psychological and technological factors in explaining human performance in the context of the group when interacting with technology. The research design was correlational predictive, with multiple linear regression data analysis technique. Participants of this study were 80 students and employees (43 males, 37 females; mean of age = 25.58 years of old, standard deviation of age = 4.92 years) who work using online collaboration tool in a virtual team. The results showed that the perceived playfulness, perceived ease of use, and xenophobia were able to predict an individual’s social loafing, but the perceived usefulness is not able to predict it. Implications of the results of research in order to prevent social loafing are stated in the Discussion section.